ERBB2 as a prognostic biomarker correlates with immune infiltrates in papillary thyroid cancer - Jin, Yuchen; Qiu, Xian; He, Ziyan; Wang, JunYao; Sa, Ri; Chen, Libo (Frontiers in Genetics, 2022)
Epidermal growth factor receptor 2 (ERBB2) is commonly over-expressed in progressive or metastatic tissues of papillary thyroid cancer (PTC) with poor prognosis, while it remains unknown whether ERBB2 plays a role in the deterioration of PTC. Thus, we analyzed the data derived from online repositories, including TCGA, KEGG, GO, GeneMANIA, and STRING, to explore the relationship between ERBB2 expression and prognosis, tumor phenotypes of interest, and immune infiltrates in PTC. Compared to normal thyroid tissue, ERBB2 was upregulated in PTC samples (p < 0.001); In comparison with the group with low expression of ERBB2, the group with high expression of ERBB2 had poorer progression-free interval in stage III/IV patients (p = 0.008) and patients aged > 45 years (p = 0.019). The upregulated ERBB2 was associated with iodine metabolism dysfunction, proliferation, metastasis, angiogenesis, and drug resistance. The expression of ERBB2 negatively correlated with enrichment scores of B cells (r = -0.176, p < 0.001), CD8+ T cells (r = -0.160, p < 0.001), cytotoxic cells (r = -0.219, p < 0.001), NK CD56dim cells (r = -0.218, p < 0.001), plasmacytoid dendritic cells (r = -0.267, p < 0.001), T cells (r = -0.164, p < 0.001), T follicular helper cells (r = -0.111, p = 0.012), gamma delta T cells (r = -0.105, p = 0.017), and regulatory T cells (r = -0.125, p = 0.005). In conclusion, ERBB2 may serve as a prognostic biomarker and an immunotherapeutic target in PTC, deserving further exploration.